Thyroid Storm in an Adolescent Girl Precipitated by Empyema Thoracis - Chirag Thakur; Prawin Kumar; Jagdish Prasad Goyal; Varuna Vyas (Oman Medical Journal, 2022)
Thyroid storm is a rare, life-threatening condition in children. We report the case of a 16-year-old girl who presented with fever, cough, chest pain, and breathing difficulty. On the initial evaluation, a working diagnosis of left-sided pneumonia with empyema was made. She also had persistent tachycardia which was out of proportion to fever, and a staring look. She was found to have a thyroid storm. Timely diagnosis and appropriate management of thyroid storm proved to be lifesaving.